Security for mobility - Mitchell, Chris J. (Institution of Engineering and Technology, 2004)
Over the last decades, mobile telecommunications has grown dramatically, from a small niche technology to a massive industry. mobile telephones are now ubiquitous, and the divisions between PCs, PDAs, mobile telephones and other mobile devices are becoming increasingly blurred. Against this background, the security of information of both the devices themselves, and the information handled by these devices, is becoming ever more important. Security for mobility pulls together up to the minute research from an international group of academics and professionals working in industry. The main text of book is divided into four parts - underlying technologies; network security; mobile code issues; application security; and the future. Each chapter of the is the collaboration of different authors, including many of the leading European experts currently working with in the field. Thus each chapter is self- contained and can be read independtly, although there are many relationships between the various chapters. The book will be of interrest to engineers and computer scientist working in security related aspects of the communications, computing and telecommunications industries , as well as postgraduate students and acdemics working within these fields.